IMPLEMENTATION OF DIRECT CASH ASSISTANCE TO VILLAGE DSIN THE MANGKI VILLAGE, CEMPA SUDISTRICT, PINRANG REGENCY - Putri Rabiah El Adawiyah; Andi Aslinda; Risma Niswaty (Universitas Negeri Makassar, 2026)
This research is a type of descriptive qualitative research and aims to find out about the Implementation of Direct Cash Assistance for Village Funds in Mangki Village, Cempa District, Pinrang Regency. Data collection techniques were carried out by interview, observation and documentation. The data analysis technique used consists of data reduction (Data Condensation), Data Presentation (Data Display), Conclutions Drawing and Verifications. The results showed that the implementation of direct cash assistance of village funds in Mangki Village, Cempa District, Pinrang Regency can be said to have gone well in accordance with the theory of George Edwards III. This can be seen from 4 sub-indicators that are running well including: a. Communication b. Resources c. Disposition d. Bureaucratic Structure. Bureaucratic Structure. One sub-indicator is still not good, namely in terms of communication. The inhibiting factor in the implementation of direct cash assistance for village funds is the community itself who does not understand this program, while the external inhibiting factor is that the process of disbursing funds from the local government is usually late, thus hampering the process of distributing this program. Implementors are expected to provide an even understanding to the community so that there is no social jealousy, program implementers must be more active in providing socialization and maintaining existing infrastructure.